2016
DOI: 10.15436/2475-6245.16.ed945
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dispersive X-ray (EDX) Microanalysis in Biomedical Research

Abstract: EditorialEDX microanalysis is a technique associated to both transmission and scanning electron microscopy that is based on the detection of characteristic X-rays generated by atoms of the specimen interacted with electrons beam [1] . Each element is able to release specific X-ray which contain information about their chemical nature [2] . The minimal detectable elemental concentration relivable with EDX apparatus is about 10 -4 mol per kg of dry specimen, where as spatial resolution ranges from approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Zinc has previously been detected in prostate tissue using X-ray microanalysis 11 , but individual prostasomes have not previously been analysed using this method. X-ray microanalysis has been reported to have a detection limit of between 10 ppm and 1000 ppm 12 depending on the element and the topology of the samples. The topology of our samples is not optimal but our results show that if zinc is present in the prostasomes it is present at a lower concentration than 1 mg/g (0.1%) dry weight.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc has previously been detected in prostate tissue using X-ray microanalysis 11 , but individual prostasomes have not previously been analysed using this method. X-ray microanalysis has been reported to have a detection limit of between 10 ppm and 1000 ppm 12 depending on the element and the topology of the samples. The topology of our samples is not optimal but our results show that if zinc is present in the prostasomes it is present at a lower concentration than 1 mg/g (0.1%) dry weight.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we applied EDX assay to human biopsies to study both the elemental composition of tissue and heavy metals associated to lung cancers (Scimeca et al a,b; Scimeca et al, ).…”
Section: Materials End Methodsmentioning
confidence: 99%
“…The scanning electron microscopy and EDX analysis [4] of new formed bone showed the absence of inflammatory cells, no/rare osteoclasts and numerous cluster of osteoblasts. Thus, we can speculate that the application of immediate load dental implant influence bone metabolism inducing the recruitment and differentiation of osteoblasts [3] . Now, we expanded our study investigating the molecular factors that support mandibular regeneration after immediate load dental implant.…”
Section: Short Communicationmentioning
confidence: 99%
“…In our recent study, we demonstrated that the bone load applied by titanium implant was able to induce the mandibular osteogenic reconstruction by studying the composition of mandibular cellular population before and after surgery [3] . The scanning electron microscopy and EDX analysis [4] of new formed bone showed the absence of inflammatory cells, no/rare osteoclasts and numerous cluster of osteoblasts.…”
Section: Short Communicationmentioning
confidence: 99%